Transparent services selecting and loading with wearable devices. (1st January 2012) - Jing, Lei; Cheng, Zixue; Zhou, Yinghui; Wang, Junbo
Several cutting-edge computing paradigms, like cloud computing (CC) and transparent computing (TC), advertise to decouple the connection between the software (service) and hardware (client). We further extend the client terminal from PC to wearable embedded devices with heterogeneous structure. Specifically, two key problems are discussed: how to seamlessly select proper service from the service pool; how to unobtrusively load the selected service onto target device. In this paper, transparent service selecting and loading architecture (TSSLA) is proposed to select the proper service from the service pool using dynamic context-matching method. Moreover, a new wireless on-demand programme loading method is proposed to load the ready-to-run programme onto the specific client, such as wearable embedded devices. The wireless programme loading method of TSSLA is implemented to indicate the feasibility of the proposal. Finally, several challenging problems through the primitive research are discussed, which should be approached through multidisciplinary effort.